2018
DOI: 10.1002/2017jc013213
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Interannual Variability in the Barrier Layer of the Bay of Bengal

Abstract: An objectively analyzed monthly gridded ocean analysis derived from a combination of satellite and in situ observations is used to describe the seasonal and interannual variability in the barrier layer thickness (BLT) over the maximum variance region in the BLT of the Bay of Bengal (BoB) for the period from 1993 to 2012. The northern BoB acquires a maximum variance in the BLT where a large river discharge flux was observed. The BLT showed strong seasonal variability with minima during April–May and maxima duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The temperature inversions occur during winter when heating in the BL by penetrative shortwave radiation is greater than the heating of the ML by the net surface heat flux and the horizontal advection (Girishkumar et al, , hereafter GK11; GK13). The IL in the BoB also depends on the equatorial remote forcing in‐terms of the coastally trapped Kelvin waves and radiated Rossby waves (RWs; Rao et al, ; (Yu et al, ; GK11; GK13; Kumari et al, , hereafter KM18). Prasad () and Anitha et al (, hereafter AN08) used the Monin‐Obukhov length (M‐O length), which determines the relative importance of mechanical mixing (wind forcing) and surface buoyancy for analyzing stability and seasonality in the BoB.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature inversions occur during winter when heating in the BL by penetrative shortwave radiation is greater than the heating of the ML by the net surface heat flux and the horizontal advection (Girishkumar et al, , hereafter GK11; GK13). The IL in the BoB also depends on the equatorial remote forcing in‐terms of the coastally trapped Kelvin waves and radiated Rossby waves (RWs; Rao et al, ; (Yu et al, ; GK11; GK13; Kumari et al, , hereafter KM18). Prasad () and Anitha et al (, hereafter AN08) used the Monin‐Obukhov length (M‐O length), which determines the relative importance of mechanical mixing (wind forcing) and surface buoyancy for analyzing stability and seasonality in the BoB.…”
Section: Introductionmentioning
confidence: 99%
“…The BL phenomenon suggests that the haline stratification may influence the amount of oceanic heat content available for air-sea interactions. Hence, it serves as an important blockade that prevents the cold thermocline water from entering the mixed layer and thus has significant impacts on the upper mixed layer heat content and the sea surface temperature (Foltz & Mcphaden, 2009;Pailler et al, 1999;Vialard & Delecluse, 1998a), precipitation and monsoon (Masson et al, 2005), tropical cyclones (Balaguru et al, 2012) and even El Niño (Maes et al, 2002(Maes et al, , 2005 and Indian Ocean Dipole (Kumari et al, 2018;Qiu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The resultant MLD shoaling then favors a thick BL between the bottom of the ML and top of the thermocline (Lukas & Lindstrom, 1991). The existence of such a thick BL in the BoB has been confirmed by observational studies (de Boyer Montégut et al, 2007;Girishkumar et al, 2011;Kumari et al, 2018;Sprintall & Tomczak, 1992;Thadathil et al, 2007). Particularly, Vinayachandran et al (2002) investigated the evolution of BL in the BoB during summer and emphasized the significant effect of advection on the formation and erosion of BL.…”
Section: Introductionmentioning
confidence: 81%
“…Particularly, Vinayachandran et al (2002) investigated the evolution of BL in the BoB during summer and emphasized the significant effect of advection on the formation and erosion of BL. Using a comprehensive data set, Thadathil et al (2007) reported that BLT in the BoB is the thickest in winter (December-February) and disappears in April and May (e.g., Kumari et al, 2018;Thadathil et al, 2007).…”
Section: Introductionmentioning
confidence: 99%